Effect of pasteurisation on sensory quality of natural soursop puree under different storage conditions - Umme, A; Bambang, S.S; Salmah, Y; Jamilah, B (Elsevier, 2001)
Pasteurisation effects on natural soursop (Annona muricata L.) puree were evaluated in terms of appearance, colour, flavour, odour, consistency and overall acceptability for 12 weeks. The packaging and storage temperature combinations used were laminated aluminium foil (LAF), lacquered can (LC) and high density polyethylene plastic bottle (HDPE) at ambient temperature (28-38°C), 15, 4 and -20°C. Results showed pasteurisation at 79°C for 69 s significantly improved the sensory colour, flavour, appearance and overall acceptability of the puree. Pasteurised puree packed in LAF at 4°C had the highest score for almost every attribute evaluated. Overall, all samples were found acceptable by judges during the 12 week storage period. The better stability, in terms of colour, consistency and flavour characteristics, of pasteurised puree packed in foil at 4°C than the frozen control could be an additional and cheap advantage for storage and transport.